SEGREGATION ANALYSIS OF MORPHOLOGICAL CHARACTER AND BIOACTIVE GENOTYPE OF RICE PLANT F3 (CEMPO SALAMET/IR64) POPULATION - Indri Gita Lestari; Mohammad Ubaidillah (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2022)
Red rice contains high anthocyanin and bioactive antioxidant compounds that prevent free radical reactions. Cempo Salamet has potential as an antioxidant source, and the characteristics are red colored grains, 4–5 months old, 169 cm plant height, 7 productive tillers per plant, and resistance to blast disease. IR64 had been developed with the following characteristics: 3 months old, 85 cm plant height, 20–35 productive tillers per plant, resistance to brown leafhoppers pigment. This study aimed to obtain information on the segregation of the F3 population from crosses between the Cempo Salamet and IR64 varieties. Research methods included preparation and maintenance with genotype analysis. PCR analysis was conducted using SSR markers with primer RM346, RM316, RM228, and RM339. The segregation in F3 plants was 50% for >130 cm plant height, 51% for 10–19 tillers per plant, 67% for 2.2 g/100-grain weight, and 33% strong red for colour intensity. The findings demonstrated that SSR markers RM346, RM339, and RM228 could validate Cempo Salamet, IR64, and F3 DNA bands. However, RM316 could not validate all DNA bands in the research sample. Beras merah mengandung antosianin yang tinggi dan senyawa bioaktif antioksidan yang mampu mencegah terjadinya reaksi radikal bebas. Cempo Salamet berpotensi sebagai sumber antioksidan yang memiliki karakteristik biji berwarna merah, umur 4–5 bulan, tinggi tanaman 169 cm, anakan produktif 7 batang, tahan terhadap penyakit blas. IR64 telah banyak dibudidayakan dengan karakteristik umur 3 bulan, tinggi tanaman 85 cm, anakan produktif 20–35 batang, tahan terhadap wereng coklat, akan tetapi tidak mengandung pigmen. Penelitian ini bertujuan mendapatkan informasi segregasi populasi F3 hasil persilangan antara varietas Cempo Salamet dan IR64. Metode penelitian meliputi persiapan dan pemeliharaan tanaman serta analisis genotipe bioaktif. Analisis PCR menggunaan marka SSR dengan primer RM 346, RM 316, RM 228, dan RM 339. Terjadi segregasi karakter morfologi pada populasi F3 yaitu diperoleh tanaman dengan tinggi >130 cm (50%), 10–19 anakan (51%), bobot 100 bulir dengan 2,2 g (67%), dan intensitas warna bulir dengan merah kuat (33%). Penelitian menunjukkan marker SSR yang dapat memvalidasi pita-pita DNA yaitu RM346, RM339, and RM228, sedangkan RM316 tidak dapat memvalidasi keseluruhan pita-pita DNA pada sampel penelitian.